Development Of The Human Reproductive System Booklet As A Supplement To Natural Science Teaching Material Class IX SMP/MTs - Fitriani Utami Putri; Skunda Diliarosta (Department of Science Education, 2021)
The purpose of this study is to produce a booklet as a supplement to independent teaching materials on the material of the human reproductive system that has met valid criteria. This research is a developmet research that uses the Plomp model consisting of preliminary research, development or prototyping phase, assessment phase. Data were analyzed qualitatively and quantitatively. At the development stage, the booklet was validated by three validators who were experts in their fields covering four aspects of eligibility, namely the aspect of content worthiness, language worthiness, feasibility of presentation and feasibility of graphics. At the assessment stage the booklet is evaluated with a one to one evaluation document. The result of expert review (validation) obtained a validity value of 86, 65% with a very valid category. The validity test on the aspect of content worthiness was 82, 85% with a valid category, the presentation aspect was 90, 66%, and the graphic aspect was 87,77% with a very valid category. The conclusion thus obtained is that the resulting booklet meets very valid criteria.